2005
DOI: 10.1590/s0100-879x2005000700004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of Bauhinia racemosa L. stem bark

Abstract: The present study was carried out to evaluate the antioxidant and antimicrobial activities of a methanol extract of Bauhinia racemosa (MEBR) (Caesalpiniaceae) stem bark in various systems. 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) radical, superoxide anion radical, nitric oxide radical, and hydroxyl radical scavenging assays were carried out to evaluate the antioxidant potential of the extract. The antioxidant activity of the methanol extract increased in a concentration-dependent manner. About 50, 100, 250, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 30 publications
5
53
1
2
Order By: Relevance
“…This is desired for the emulsions preparation, since most of the desired effects are mediated by antioxidants. Our data is in accordance to what is reported by Kumar et al (2005), in which a methanol extract of Bauhinia racemosa preserved its antioxidant and total phenolic content after processing.…”
Section: Discussionsupporting
confidence: 93%
“…This is desired for the emulsions preparation, since most of the desired effects are mediated by antioxidants. Our data is in accordance to what is reported by Kumar et al (2005), in which a methanol extract of Bauhinia racemosa preserved its antioxidant and total phenolic content after processing.…”
Section: Discussionsupporting
confidence: 93%
“…M. indica extract was found least effective among all the extracts used. Present results are in harmony with the fi ndings of Kumar et al (2005) and Alberts et al (2006). They reported that pre-and post-harvest bio-deterioration of crop seeds are mainly due to seed infestation by microorganisms and insects, causing up to 100% losses.…”
Section: Discussionsupporting
confidence: 88%
“…54 Preliminary bioassays indicated that the methylene chloride extracts of the seeds of both species had antifungal activity against Colletotrichum fragariae. Examples of other antifungal crude extracts from medicinal species also included Bauhinia racemosa L. (Caesalpiniceae) stem bark, 55 the latex of gazyumaru (Ficus microcarpus L., Moraceae), 56 Larrea divaricata Cav. (Zygophyllaceae) which presented fungitoxic activity against yeasts and fungi, 57 and leaf extracts of Tapinanthus sessilifolius (P. Beauv) Van Tiegh.…”
Section: Crude Extractsmentioning
confidence: 99%